Penguatan Kapasitas Guru TPQ melalui Pembinaan Tahfidzul Qur’an di TPQ Al Qolam Paciran Lamongan - Tri Tami Gunarti; Mubarok Ahmadi; Dini Maulidhah (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2025)
This community service program aims to enhance the professional capacity of teachers at TPQ Al-Qolam in Kranji Village, Paciran, Lamongan, through structured tahfidzul Qur’an coaching. The program was conducted over four weeks with eight coaching sessions, employing participatory and interactive approaches. The primary focus of the coaching was strengthening mutqin memorization techniques and murāja‘ah practices through interactive methods, including regular repetition, understanding the meaning of verses, writing Qur’anic verses, and utilizing instructional media. The results indicate a significant improvement in teachers’ memorization abilities, self-confidence, and motivation to develop a sustainable tahfidz culture. Challenges encountered included time constraints, age-related factors, and adaptation to new methods; however, these were effectively addressed through intensive mentoring and reflective discussion forums. This program not only improved technical skills but also reinforced teachers’ identities as Qur’anic educators. The activity is recommended for replication in other TPQs to support the enhancement of Qur’anic education quality at the grassroots level.